2005
DOI: 10.1080/02646830512331330938
|View full text |Cite
|
Sign up to set email alerts
|

Associations between child development and women's attitudes to pregnancy and motherhood

Abstract: A woman's psychological state during pregnancy has been shown in previous research to be predictive of her adaptation to maternal functioning. Two hypotheses were examined: (a) women who have a negative attitude to pregnancy and motherhood have children who exhibit slower development at 2 years, compared with children of women who have more positive attitudes; (b) women with poor psychological health antenatally have children who exhibit slower development at 2 years, compared with children of women who have g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…They can be simple or more complex, often filled with romantic ideas of what parenthood might be like (Pancer et al, 2000). It has been previously shown that there is an association between a woman's antenatal psychological state and her adaptation for maternal functioning (Coleman, Nelson, & Sundre, 1999;Deave, 2005). The theoretical part of this publication aims to describe maternal attitudes shaped in the prenatal period of the child's development.…”
Section: Measurementmentioning
confidence: 99%
See 4 more Smart Citations
“…They can be simple or more complex, often filled with romantic ideas of what parenthood might be like (Pancer et al, 2000). It has been previously shown that there is an association between a woman's antenatal psychological state and her adaptation for maternal functioning (Coleman, Nelson, & Sundre, 1999;Deave, 2005). The theoretical part of this publication aims to describe maternal attitudes shaped in the prenatal period of the child's development.…”
Section: Measurementmentioning
confidence: 99%
“…The rise of prenatal psychology and reproductive psychology, however, has brought attention to the importance of formation of maternal attitudes, for the development of the mother-child relations during pregnancy and in the early neonatal period (DiPietro, Novak, Costigan, Atella, & Reusing, 2006;Bor, Brennan, Williams, Najman, & O'Callaghan, 2003;Kumar et al, 1984;BielawskaBatoro wicz, 1999BielawskaBatoro wicz, , 2006Kornas-Biela, 2009). Research shows that prenatal and postnatal attitudes of women towards pregnancy, motherhood and the child have an influence on the subsequent emotional and cognitive development of the child (Hutchinson et al, 2008;Deave, 2005). A negative attitude towards pregnancy and child care is correlated with later health and developmental problems of the child (Bor et al, 2003;Wilkins et al, 2004;Deave, 2005).…”
Section: Measurementmentioning
confidence: 99%
See 3 more Smart Citations